A “tendência à sinceridade” de Prudente de Moraes, neto: um vazio na ensaística de nacionalidade brasileira (Revista de Crítica Literaria Latinoamericana, 2019)
This article investigates the impacts of Prudente de Moraes, neto’s conception of “sincerity” in three different occasions of Brazilian nationalist essayism: firstly on the “valorização do preto”, of Gilberto Freyre; secondly on the idealization of the “cordial man”, by Sergio Buarque de Holanda; and, finally, on the debates realized by the review Cultura Política under the years of the Estado Novo (1937- 1945). This “sincerity” does not consist in any kind of intimacy or even in some moralism promoted by the author. On the contrary, it is one of the main out- spreads of the surrealist André Breton’s poetics and of the conceps of Freud in the Brazilian context.
Keywords: Prudente de Moraes; neto; essay; nationalism; surrealism; sincerity